Traumatic Experiences, Stressful Events, and Alexithymia in Chronic Migraine With Medication Overuse - Bottiroli, Sara; Galli, Federica; Viana, Michele; Sances, Grazia; Tassorelli, Cristina (Frontiers in Psychology, 2018)
Background: Many factors are involved in the prognosis and outcome of Chronic Migraine and Medication Overuse Headache (CM+MOH), and their understanding is a topic of interest. It is well known that CM+MOH patients experience increased psychiatric comorbidity, such as anxiety, depression, or personality disorders. Other psychological factors still need to be explored. The present study is aimed to evaluate whether early life traumatic experiences, stressful life events, and alexithymia can be associated with CM+MOH. Methods: Three hundred and thirty-one individuals were recruited for this study. They belonged to one of the two following groups: CM+MOH (N=179; 79% females, Age: 45.2 ± 9.8) and episodic migraine (EM) (N=152; 81% females; Age: 40.7 ± 11.0). Diagnosis was operationally defined according to the International Classification of Headache Disorders 3rd edition (ICHD-IIIβ). Data on early life (physical and emotional) traumatic experiences, recent stressful events and alexithymia were collected by means of the Childhood Trauma Questionnaire, the Stressful life-events Questionnaire, and the Toronto Alexithymia Scale (TAS-20) respectively. Results: Data showed a higher prevalence of emotional (χ² = 6.99; d.f. = 1; p = .006) and physical (χ² = 6.18; d.f. = 1; p = .009) childhood trauma and of current stressful events of important impact (χ² = 4.42; d.f. = 1; p = .025) in CM+MOH patients than in EM ones. CM+MOH patients were characterized by higher difficulties in a specific alexithymic trait (Factor 1 subscale of TAS-20) (F(1, 326) = 6.76, p = 0.01, ηp² = .02) when compared to the EM group. The role of these factors was confirmed in a multivariate analysis, which showed an association of CM+MOH with emotional (OR 2.655; 95% CI 1.153-6.115, p = .022) or physical trauma (OR 2.763; 95% CI 1.322-5.771, p = .007), and a high score at the Factor 1 (OR 1.039; 95% CI 1.002-1.078, p = .040). Conclusions: Our findings demonstrated a clear relationship between CM+MOH and life traumas, stressful events, and alexithymia. These observations have a relevant role in multiple fields of related to chronic headache: from the management to the nosographic framing.